Perancangan Lemari Pendingin Berbahan Insulasi Musicool-22 - Nugroho, Adi; Azharman, Zefri; Meldra, Delia; Triana, Yuyun (LPPM-ITEBA, 2024)
The purpose of this research is to modify the design of a cooling product and combine it with a new, environmentally friendly insulation that does not harm the ozone layer. In this study, data collection techniques include a literature review from various books and journals. The cooling box in this design uses hydrocarbon refrigerant, namely musicool-22, with polyurethane insulation of 1.75 m thickness and a capacity of 95 kg, resulting in a cooling load of 8768.951 W. A 3HP compressor is used, generating a refrigeration impact of 370 kJ/kg, a refrigerant flow rate of 0.018 kg/s, compressor power of 1080 watts, COP of 6.24, and an estimated cooling time of approximately 1.108 hours.